The Influence of Bioinsektiidide Variation of Tuba Root Extract (Derris elliptica Roxb. Benth) On Phantsahm Mortality the Pest (Leptocorisa Acuta Thumberg) - I Gede Warse; Handoko Santoso; Rasuane Noor (UNIVERSITAS NEGERI PADANG, 2019)
Leptocorisa acuta Thumberg is one of the pests that many rice farmers complain about. This pest can cause damage to rice plants while still young, so the results obtained are not optimal. Based on these problems it is necessary to use insecticides so that the pest can be controlled. Derris elliptica Roxb. Benth is one of the many plants that grow in Indonesia. The root of this plant has a chemical compound in the form of rotenone which has the potential as a bioinsecticide to eradicate pest parasites. The study was an experimental study using a completely randomized design method with three treatments and one control with 6 replications. The treatment dose in this study using root extract Derris elliptica Roxb. Benth. Bent: 8%, 10%, 12% and 0% control. Based on the Kruskal Wallis Test the results were x2calculate 10.88 > x2table 9.49 at a 0.05 in the Chi-square table, so that there was an effect of the variation of the bioinsecticide dose of root extract Derris elliptica Roxb. Benth the impact on mortality of the Imago Leptocorisa acuta Thumberg. Based on the average ranking of treatment at a dose of 12%: 6.7, a dose of 10%: 8.46, a dose of 12%: 8.76 and a control of 0%: 18, so it can be concluded that root extract Derris elliptica Roxb. Benth the most effective against the mortality of imago Leptocorisa acuta Thumberg was at a dose of 12%.